Categories of being essays on metaphysics and logic - Haaparanta, Leila, 1954-; Koskinen, Heikki J. (New York ; Oxford : Oxford University Press, 2012)
This volume is a comprehensive presentation of views on the relations between metaphysics and logic from Aristotle through philosophers who contributed to the return of metaphysics in the analytic tradition.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Categories (Philosophy) -- History